Analog of giant magnetoimpedance in magnetized ε-near-zero plasma - Shen, Lian (2020)
In this Letter, we show that magnetized plasma with properly designed parameters at plasma frequency suffers a large magnetoimpedance change under a moderate external magnetic field. Such an interesting feature can be described as the analog of giant magnetoimpedance (GMI), which is confirmed by detailed calculation. GMI devices based on magnetized -near-zero plasma do not require microfabrication, and they are capable of working at tunable frequency, even in terahertz frequency range; more importantly, they can be dynamically controlled by environmental parameters such as temperature and pressure.